HUBUNGAN POLA ASUH ORANG TUA DENGAN KECERDASAN EMOSIONAL PADA REMAJA : LITERATURE REVIEW - Firman Pangestu, Prayoga; N. Bolla, Ibrahim; Pragholapati, Andria (Journal Healthcare Education, 2023)
Generally adolescents often experience emotional changes call is storm and stress conditions, therefore, demanding not only intellectual or cognitive intelligence, but also emotional intelligence for recognizing and controlling emotion. adolescent have bad or good emotional intelligence is relate to several important factors that influence it, one of theme is family environment in which the parenting style that parents give to their children to step on adolescent. Objective: this study puspose to find out corelation pattern of parenting with emotional intelligence to adolescent Method: This study used a literature review with sistematic review design. Search tool uses GoogleScholar Garuda, PubMed, Science direct and online library. The keywords use are parenting, adolescent,and emotional intelligence. Criteria for selecting sources include journal articles or books about parenting and emotional intelligence to adolescents, journals indexed in Sinta and ScimagoJr, open access journal or journal full text, year of publication from 2010 up to 2020 with primary data. The search results obtained 10 journals that qualify of criteria, then the data were analyzed using descriptive methods. Result: Parenting patterns have a significant impact on the development of adolescent emotional intelligence. It is necessary to treat a balance between the dimensions of warmth and controlling in guiding them. This can help improve the development of emotional intelligence for the better.